Stability of biodegradable metal (Mg–Ca–Zn alloy) screws compared with absorbable polymer and titanium screws for sagittal split ramus osteotomy of the mandible using the finite element analysis model. Issue 10 (October 2017) - Lee, Jee-Ho; Han, Hyung-Seop; Kim, Yu-Chan; Lee, Jin-Yong; Lee, Bu-Kyu
Abstract: Mg–Ca–Zn alloy has been suggested for the application of fixation materials during maxillofacial surgery. We investigated the stability of Mg–Ca–Zn alloy for clinical application during orthognathic surgery. The finite element model for the fixation of sagittal split ramus osteotomy was constructed. In the bicortical screw fixation of the mandible setback condition, the stress distributions of Mg–Ca–Za alloy, polylactic acid polymer, and titanium were evaluated using the virtual model with occlusal loading of 132 N. The deformations of the three different materials of fixation screw were observed according to masticatory force ranging from 132 to 1, 000 N. When comparing the stress distribution placed on cortical bone between the polymer and magnesium alloy groups, the magnesium alloy screws could bear more stress, thereby decreasing the stress, which might be distributed to other biologic components, such as the condyle and cortical ramus of the mandible. Deformations of the screws according to functional load were minimal, and the deformation remained <0.21 mm at the initial functional load of the mandible after surgery, regardless of materials used. The biodegradable magnesium alloy screw can bear more stress and decrease the detrimental effect on the stability of sagittal split ramus osteotomy setback surgery.